2006
DOI: 10.1109/lcomm.2006.1576558
|View full text |Cite
|
Sign up to set email alerts
|

Power delay profile and noise variance estimation for OFDM

Abstract: Abstract-In this letter, we present cyclic-prefix (CP) based noise-variance and power-delay-profile estimators for Orthogonal Frequency Division Multiplexing (OFDM) systems. Signal correlation due to the use of the CP is exploited without requiring additional pilot symbols. A heuristic estimator and a class of approximate maximum likelihood (ML) estimators are proposed. The proposed algorithms can be applied to both unitary and non-unitary constellations. These algorithms can be readily used for applications s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
89
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 70 publications
(90 citation statements)
references
References 7 publications
1
89
0
Order By: Relevance
“…Moreover, in opposition to non data-aided estimator such as [5], it is not based on the subjective choice of a threshold level. However, compared to the Modified ESE method, the estimator derived in this section suffers from the drawbacks of requiring prior time and frequency synchronization and is dependent on the CP and channel impulse response durations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, in opposition to non data-aided estimator such as [5], it is not based on the subjective choice of a threshold level. However, compared to the Modified ESE method, the estimator derived in this section suffers from the drawbacks of requiring prior time and frequency synchronization and is dependent on the CP and channel impulse response durations.…”
Section: Discussionmentioning
confidence: 99%
“…It can be easily shown that the estimator with the smallest variance is found for u = L. The difficulty is then to estimate L. Cui et al suggested an estimator in [5] 2 for NDA OFDM synchronization algorithms refer to [3] and [4] but…”
Section: Algorithmmentioning
confidence: 99%
“…This estimator has the major advantage of being independent of any threshold level and shows good performance compared to the threshold-based technique proposed in [14]. Here presented method has a computational complexity (C.C) of O(M s .D 2 ).…”
Section: Noise Power Estimationmentioning
confidence: 97%
“…Indeed, underestimating the SNR and not connecting to the access point are much better than overestimating it, and then we find that the QoS does not satisfy our needs and wasting time again finding other potential candidates. We point out that the method presented in [14], as our method, also requires a perfect time-frequency synchronization.…”
Section: Signal Power Estimationmentioning
confidence: 99%
“…This is not unexpected as is seen from [8], where the noise power is used to estimate the TO. The study on the noise power estimation can be found from [14] and references therein.…”
Section: ) Mle1mentioning
confidence: 99%